Doses of rituximab for retreatment in rheumatoid arthritis: influence on maintenance and risk of serious infection. (15th December 2017) - Henry, Julien; Gottenberg, Jacques-Eric; Rouanet, Stéphanie; Pavy, Stephan; Sellam, Jeremie; Tubach, Florence; Belkhir, Rakiba; Mariette, Xavier; Seror, Raphaèle; ,
Abstract: Objective: To investigate maintenance of rituximab (RTX) in RA patients re-treated with reduced doses compared with standard dose in a real life setting. Methods: The Autoimmunity and Rituximab (AIR) registry is a nationwide prospective observational cohort investigating the long-term safety and efficacy of RTX in RA. The present study included patients from the AIR registry that have been re-treated with RTX after a first course of RTX standard dose (1000 mg × 2). Two groups were defined according to dose of RTX of the first retreatment course (i.e. second course): standard dose group and reduced dose group. Five years' maintenance and rate of serious infections of the retreatment period were compared between standard dose and reduced dose groups. Analyses used the inverse probability of treatment weighting propensity score adjusted method. Results: Among the 1986 patients from the AIR registry, 1278 were included, 1093 (85.5%) treated with standard dose and 185 (14.5%) with reduced doses. Maintenance of RTX at 5 years in the standard and reduced groups was 55.5 and 53.8%, respectively, and did not significantly differ between groups in adjusted analyses (hazard ratio = 1.03; 95% CI: 0.81, 1.30), but the cumulative RTX dose received for retreatment [1.4 (0.6) vs 2.3 (1.0) g/year, P < 0.001] and the rate of serious infections were significantly lower in the reduced dose group (adjusted hazard ratio = 0.50; 95% CI: 0.27, 0.92; P = 0.02). Conclusion: Use of reduced doses of RTX for retreatment did not alter the maintenance of RTX at 5 years in RA patients, but allowed a 39% total dose reduction and a lower rate of serious infections.